1993
DOI: 10.1007/bf01476283
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in chronic subdural haematoma

Abstract: We studied retrospectively 143 adult patients treated in our department from 1979 to 1991 for chronic subdural haematoma (SDH) in order to identify the incidence of seizures and the necessity for prophylactic anticonvulsant treatment. Furthermore, after review of the literature, we selected an additional 879 cases for comparison. Results indicated a low incidence of epilepsy. Before surgery 5.6% of patients in our series and 4.3% in the literature had epilepsy, whereas after surgery, the frequencies were 3% an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 37 publications
1
46
1
2
Order By: Relevance
“…Two studies reported no significant difference in seizure rate secondary to the prophylactic administration of AEDs [64,73]. Both groups concluded that the morbidity of AED administration outweighs the benefits except in patients at particularly high risk for seizures, such as alcoholics [64,73].…”
Section: Prophylactic Anticonvulsants Following Csdhmentioning
confidence: 95%
See 1 more Smart Citation
“…Two studies reported no significant difference in seizure rate secondary to the prophylactic administration of AEDs [64,73]. Both groups concluded that the morbidity of AED administration outweighs the benefits except in patients at particularly high risk for seizures, such as alcoholics [64,73].…”
Section: Prophylactic Anticonvulsants Following Csdhmentioning
confidence: 95%
“…Therefore, the added risk of recurrent hemorrhage following anticonvulsant treatment must be outweighed by the benefits of AED prophylaxis. Unfortunately, the efficacy of seizure prophylaxis in the setting of both treated and untreated cSDH has been addressed only through a small number of retrospective studies [24,64,73,76].…”
Section: Prophylactic Anticonvulsants Following Csdhmentioning
confidence: 99%
“…Rubin and Rappaport [102] conducted a retrospective analysis of 143 adult patients treated for CSH from January 1979 to July 1991. Surgeries were performed on 138 patients.…”
Section: Discussionmentioning
confidence: 99%
“…For some experts, the low incidence of seizures does not justify an anticonvulsant prophylaxis in patients with CSH caused by minor head injury [83]. Others suggest that this prophylactic medication should be considered only in alcoholic patients because of their higher risk of seizure [102]. Another study verified a significant increase in morbidity and mortality associated with respiratory complications and status epilepticus in patients with new-onset seizures.…”
Section: Introductionmentioning
confidence: 97%
“…This information greatly favors the use of prophylactic AEDs in acute SDH. Reduction of seizures from the prophylactic use of AEDs in chronic SDH is more controversial [12,13,15,56,57]. Although AEDs are not routinely used in this setting in the absence of a clinical suspicion of seizures, seizures should always be considered when the clinical progress is not as anticipated.…”
Section: Treatmentmentioning
confidence: 97%